2017
DOI: 10.1016/j.jcin.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography–Guided Full Plastic Jacket in Spontaneous Coronary Artery Dissection

Abstract: A healthy 38-year-old woman was hospitalized for an acute coronary syndrome. Coronary angiography revealed a smooth, diffusely narrowed right coronary artery ( Figure 1A). With an adequate level of suspicion, optical coherence tomography (OCT) was performed and identified sponta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Intracoronary imaging (IVUS/OCT) has theoretical advantages over coronary angiography; nonetheless, a large coronary imaging series confirmed a small number of complications (5 of 63 cases) directly attributable to intracoronary imaging, resulting in either false lumen propagation, impaired flow, or iatrogenic dissection. 44,45 When compared to OCT, imaging with IVUS does not require high-pressure injection of contrast and presents with a safer diagnostic profile. However, its lower spatial resolution makes it challenging to distinguish SCAD from lipid-rich atheroma (a key differential diagnosis).…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary imaging (IVUS/OCT) has theoretical advantages over coronary angiography; nonetheless, a large coronary imaging series confirmed a small number of complications (5 of 63 cases) directly attributable to intracoronary imaging, resulting in either false lumen propagation, impaired flow, or iatrogenic dissection. 44,45 When compared to OCT, imaging with IVUS does not require high-pressure injection of contrast and presents with a safer diagnostic profile. However, its lower spatial resolution makes it challenging to distinguish SCAD from lipid-rich atheroma (a key differential diagnosis).…”
Section: Discussionmentioning
confidence: 99%
“…OCT proved to be able to identify the rupture site (the entry tear), visualise the intimo-medial membrane and comprehensively assess the characteristics, extent and distribution of the true and false lumen/IMH.The technique could also be used to disclose the involvement of related side branches and the presence of thrombus in the false or the true lumen. Other studies have confirmed the utility of OCT as a diagnostic tool as well as for guiding PCI [61][62][63][64]. Jackson et al described unique OCT findings in a larger series of 65 SCAD patients.…”
mentioning
confidence: 88%